2021
DOI: 10.1097/gco.0000000000000759
|View full text |Cite
|
Sign up to set email alerts
|

Update in palliative care in gynecologic oncology

Abstract: Purpose of reviewThis review summarizes research advances in quality of life, symptom management, and end-of-life practices within palliative care that can benefit patients with gynecologic cancers. Recent findingsAddressing fertility issues, sexual side effects, and possible disease recurrence can promote quality of life in gynecologic cancer survivors. Cannabis can provide some benefit for nausea and neuropathic pain, yet for nonneuropathic pain presentations, it does not appear to provide significant benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…While no definitive preferred screening tool emerged in either setting for this population of patients, many of the screening methods are worthy of further evaluation. Recent updates in gynecologic oncology patients have also revealed that presence of hypercalcemia, shorter period of remission before disease recurrence, and recurrent hospitalizations for either pleural effusion(s) or ascites portend poorer prognosis; therefore, addition of these criteria to clinical trigger tools may be fruitful in identification of patients who would benefit from specialty PC consultation (40). Future research should aim to further refine screening tools across treatment settings, with another potential area of exploration being the development of a dualpronged assessment (completed by provider and patient) to identify patients that would benefit from PC involvement.…”
Section: Discussionmentioning
confidence: 99%
“…While no definitive preferred screening tool emerged in either setting for this population of patients, many of the screening methods are worthy of further evaluation. Recent updates in gynecologic oncology patients have also revealed that presence of hypercalcemia, shorter period of remission before disease recurrence, and recurrent hospitalizations for either pleural effusion(s) or ascites portend poorer prognosis; therefore, addition of these criteria to clinical trigger tools may be fruitful in identification of patients who would benefit from specialty PC consultation (40). Future research should aim to further refine screening tools across treatment settings, with another potential area of exploration being the development of a dualpronged assessment (completed by provider and patient) to identify patients that would benefit from PC involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ovarian cancer may receive a variety of chemotherapy and targeted therapy agents (see Chemotherapy and targeted therapy). Surgical recovery 1,4,10,27,[37][38][39][40][41] Cytoreduction and simultaneous resection of other body tissues and organs may take 6 to 12 hours. The patient is hospitalized from 3 to 7 days.…”
Section: Chemotherapy and Targeted Therapymentioning
confidence: 99%
“…Infection 1,4,10,26,27,[37][38][39][40][41] Patients are at increased risk for infection related to chemotherapy and surgery. The infection risk is greatest when they reach their absolute neutrophil count (ANC) nadir, 7 to 14 days after a chemotherapy cycle.…”
Section: Chemotherapy and Targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest that long-term cannabis consumption is associated with negative psychological and physiological health outcomes (Fergusson & Boden, 2008; Horwood et al, 2010; Hyggen, 2012), although such conclusions are far from unanimous. Recent findings also show that cannabis can have beneficial medical effects, such as enhancing the analgesic effect of opiates, reducing nausea, and decreasing seizure frequency in patients with epilepsy (Cooper et al, 2018; García-Peñas et al, 2021; Karlin et al, 2022; Xu et al, 2021). Although there is general consensus in the field that acute and nonacute consumption of cannabis can impair episodic memory, studies evaluating components of executive functioning have produced more equivocal results (Dellazizzo et al, 2022).…”
mentioning
confidence: 99%